2014
DOI: 10.1056/nejmoa1303646
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Pregabalin with Pramipexole for Restless Legs Syndrome

Abstract: Pregabalin provided significantly improved treatment outcomes as compared with placebo, and augmentation rates were significantly lower with pregabalin than with 0.5 mg of pramipexole. (Funded by Pfizer; ClinicalTrials.gov number, NCT00806026.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
97
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 189 publications
(105 citation statements)
references
References 33 publications
2
97
0
4
Order By: Relevance
“…A landmark clinical trial in 2014 compared 300 mg of pregabalin (a calcium channel α2δ ligand) against pramipexole for RLS. This study showed that pregabalin was more effective than pramipexole 0.25 mg (but not 0.5 mg) and did not have the long-term complication of augmentation 40. However, the drop-out rate due to adverse events was higher with pregabalin.…”
Section: Introductionmentioning
confidence: 65%
“…A landmark clinical trial in 2014 compared 300 mg of pregabalin (a calcium channel α2δ ligand) against pramipexole for RLS. This study showed that pregabalin was more effective than pramipexole 0.25 mg (but not 0.5 mg) and did not have the long-term complication of augmentation 40. However, the drop-out rate due to adverse events was higher with pregabalin.…”
Section: Introductionmentioning
confidence: 65%
“…The rate of augmentation over a period of 40 or 52 weeks was significantly lower with pregabalin than with pramipexole at a dose of 0.5 mg (2.1% v 7.7%; P=0.001) but not at a dose of 0.25 mg (2.1% v 5.3%; P=0.08). 144 Opiates Oxycodone extended release Oxycodone is considered effective in treatment resistant RLS/WED on the basis of one class II study that co nsisted of a high quality 12 week, randomised, double blind, placebo controlled phase (n=304) followed by a 40 week open label extension (n=197). Prolonged release oxycodone-naloxone (5.0 mg/2.5 mg twice daily uptitrated to a maximum dose of 40 mg/20 mg twice daily) was shown to be effective in RLS/WED refractory to other treatments.…”
Section: Diagnosis Of Rls/wedmentioning
confidence: 99%
“…153 However, even low dose dopaminergic treatments carry a risk of augmentation. 144 Physicians should explain to patients that the goal of treatment is not to eradicate symptoms At the beginning of treatment with dopamine agonist, pre-existing fluctuations in symptom severity cease and initial therapeutic benefit is obtained. However, with longer duration of treatment these fluctuations will eventually re-emerge until the severity matches or even exceeds that before any treatment had been started.…”
Section: Fluctuating Rls/wed Symptomsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the high prevalence of pain and other comorbid conditions in MS, alpha-2-delta-ligands are attractive alternatives. Anticonvulsants, including gabapentin, carbamazepine, and most recently pregabalin [83] have been shown to be effective treatments for RLS and may be ideal choices for patients who suffer from concomitant conditions such as neuropathic pain or seizures, for patients who experienced augmentation on dopaminergic agents.…”
Section: Motor Disorders Of Sleepmentioning
confidence: 99%